2018
DOI: 10.3897/zookeys.746.15140
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian obligatory subterranean fauna and threats to the hypogean environment

Abstract: The subterranean environment harbors species that are not capable of establishing populations in the epigean environment, i.e., the obligatory subterranean species. These organisms live in a unique selective regime in permanent darkness and usually low food availability, high air humidity in terrestrial habitats, and low temperature range allied to other unique conditions related to lithologies and past climatic influences. The pressure to increase Brazil’s economic growth relies on agricultural/pastoral indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 29 publications
1
41
0
2
Order By: Relevance
“…Below we present an identification key to the Potamolithus from the Alto Ribeira karst area in São Paulo State: With more than 60 troglobitic species, the Alto Ribeira is a high-diversity area for troglobites (sensu Trajano et al 2016, Gallão andBichuette 2018). This is among the highest genetic diversities recorded for Brazil, and is likely related to three factors: the high degree of habitat fragmentation, limited mobility leading to low capacity for dispersal, and habitat preferences.…”
Section: Resultsmentioning
confidence: 99%
“…Below we present an identification key to the Potamolithus from the Alto Ribeira karst area in São Paulo State: With more than 60 troglobitic species, the Alto Ribeira is a high-diversity area for troglobites (sensu Trajano et al 2016, Gallão andBichuette 2018). This is among the highest genetic diversities recorded for Brazil, and is likely related to three factors: the high degree of habitat fragmentation, limited mobility leading to low capacity for dispersal, and habitat preferences.…”
Section: Resultsmentioning
confidence: 99%
“…The historical bias of speleology and taxonomy towards European and North American cave faunas is uncontested (cf. Moldovan 2012, Deharveng and Bedos 2012, Gallão and Bichuette 2018. Nevertheless, for certain taxa such as most insects the trend towards a relatively low diversity in tropical caves does not seem to disappear with a more comprehensive study of tropical faunas.…”
Section: Tropical Versus Temperate Cavesmentioning
confidence: 99%
“…According to "around 1000 troglobiomorphic spiders have been classified as troglobionts". However, a recent overview of the Brazilian obligatory subterranean fauna found that over 50% of troglobionts available in collections remain undescribed (Gallão and Bichuette 2018), suggesting that the actual number is much higher. Whatever the species numbers, compared to some other major groups like isopods, amphipods, carabid and leiodid beetles, salamanders, and fish, subterranean spiders have rarely been studied in much detail or propagated as model organisms for particular questions concerning evolution in subterranean environments (for exceptions, see .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to P. canastra sp. nov., two more subterranean species are known from the Serra da Canastra (different taxonomic group) that has been sampled by LES team (Laboratório de Estudos Subterrâneos) since 2009 (Gallão and Bichuette 2018). This shows the potential and biospeleological importance of the region, as well as the need for adequate protection and management of the cave, its surroundings, the watershed and landscape (Gallão and Bichuette 2018).…”
Section: Endemism and Conservationmentioning
confidence: 99%